Project green pharmacy: a pilot study in best practices for medicine waste disposal in households - Ghanshamnani, Lata; Motwani, Pooja; Kulkarni, Vrushali V.; Mhatre, Deepali (International Journal Of Community Medicine And Public Health, 2025)
Background: Pharmaceutical waste disposal poses significant environmental and public health concerns, particularly in urban regions where improper practices result in ecosystem contamination and human health risks. In India, discarded or expired medicines, including antibiotics and painkillers, are commonly disposed of in landfills or flushed, exacerbating pollution. The Green Pharmacy initiative by RNisarg Foundation in Thane City was developed to address these issues through public education, secure disposal infrastructure, and waste segregation. Methods: A cross-sectional study evaluated three-year campaign (2022-2024), which utilized digital (webinars, videos, flyers) and physical (on-ground sessions, live demonstrations) engagement strategies to promote safe disposal and responsible purchasing of pharmaceuticals. Initially, 30 tamper-proof bins were placed in commercial complexes, chemist shops, and residential societies for collection. Later, an additional 170 bins were deployed within a 1-kilometer radius across the city to improve participation and collection efficiency. Results: The campaign successfully reached over 20,000 individuals. Structured interviews revealed that 100% of participants had previously engaged in unsafe disposal practices, with 90% discarding medicines in landfills and 10% flushing them. Over the study period, 1,979.1 kg of pharmaceutical waste was collected, comprising 67.72% active pharmaceutical ingredients (APIs) and 32.28% packaging waste. Waste contributions were 47% from commercial complexes, 37% from residential societies, and 16% from chemists. Conclusions: The Green Pharmacy initiative demonstrated significant impact in improving public awareness and disposal practices. Sustained community engagement, policy reinforcement, and recycling measures are essential to mitigate pharmaceutical pollution and its associated health risks in India.